HUBUNGAN ANTARA KONFORMITAS KELOMPOK SEBAYA DENGAN PERILAKU MEROKOK PADA SISWA SMK NEGERI 1 SUMBAWA BESAR - Ririn Solehah; Lukmanul Hakim; Roni Hartono (Fakultas Psikologi dan Humaniora- Universitas Teknologi Sumbawa, 2019)
This research aims to find out how the relationship between peer group conformity with the smoking behavior in the students grade SMKN 1 Sumbawa. This research uses a quantitative approach. Taking the subject of the research is done using the approach of study population with a total of 60 people in SMKN 1 Sumbawa. Research data obtained by using a research instrument in the form of two scale i.e. conformity scale peers and the behavior of smoke. Peer conformity scale consists of 25 items with validity coefficients between 0.301 until 0.598 and reliability coefficient of 0.818. While the scale of the smoking behaviour consists of 29 items with validity coefficients between up to 0.305 0.610 and reliability coefficient of 0.816. The results of this research show that the existence of a relationship (correlation) is negative with 0.363 (called r empirical or re). With the number of the subject as many as 60 people (N = 60). A correlation can be seen from the p value 0.05 to calculate < showed a significant relationship. Based on the analysis of the data, i.e. calculate p value obtained of 0.004 which means that p = 0.004 < 0.05 and this shows the relationship or correlation is significant.